Incremental Prognostic Value of Systemic Immune-Inflammation Index Over GRACE and TIMI Scores in Acute Coronary Syndrome: A Meta-Analytical Approach - Veronica Fetrina Purwanti Saputro; Yessi Mayke (HM Publisher, 2026)
Current risk stratification in acute coronary syndrome relies heavily on the Global Registry of Acute Coronary Events (GRACE) and Thrombolysis in Myocardial Infarction (TIMI) scores. These models insufficiently account for systemic inflammatory burden. The Systemic Immune-Inflammation Index has emerged as a promising hematological biomarker to address this gap. A systematic literature search and quantitative meta-analysis were conducted following PRISMA guidelines. Six clinical studies focusing on the Systemic Immune-Inflammation Index and GRACE/TIMI scores in acute atherosclerotic conditions were included. Data were pooled utilizing a random-effects model to calculate the Standardized Mean Difference of index levels between high-risk and low-risk patient cohorts. The pooled meta-analysis demonstrated significantly elevated Systemic Immune-Inflammation Index levels in patients who subsequently experienced Major Adverse Cardiovascular Events compared to those who did not, yielding an overall Standardized Mean Difference of 1.12 (95 percent confidence interval: 0.99 to 1.25, p less than 0.001). Qualitative synthesis revealed that integrating this index into the GRACE and TIMI models yielded significant improvements in the Area Under the Curve, Net Reclassification Improvement, and Integrated Discrimination Improvement metrics. In conclusion, the addition of the Systemic Immune-Inflammation Index to conventional scoring systems significantly improves prognostic accuracy and risk reclassification for patients presenting with acute coronary syndrome. It serves as an accessible biomarker capturing residual inflammatory risk undetected by standard clinical models.